Implementation of City Minimum Wage Payments for Household Assistants in Kuanino Village, Kota Raja District, Kupang City - Nono, Carolin P.; Agustinus Hedewata; Darius Mauritsius (Indonesian Journal of Contemporary Multidisciplinary Research, 2024)
One of the rights as a worker is getting a wage based on the City Minimum Wage standard which is not available to household assistants. This research aims to determine the implementation of the payment of the city minimum wage and the factors that influence the non-payment of the city minimum wage for household assistants in Kuanino Village, Kota Raja District, Kupang City. This research uses empirical legal methods. The results of the research show that the implementation of the payment of the city minimum wage has not been implemented for household assistants because its determination and implementation cannot yet be aimed at household assistants and the factors that influence its non-implementation consist of internal factors in the form of economic conditions/paying ability of the employer, the amount of work done by workers, lack of family finances from job seekers, self-competence of workers, bargaining power of workers and age of workers and external factors in the form of government regulations, lack of data collection and lack of supervision/monitoring